Mixed Convection Flow Adjacent to a Stretching Vertical Sheet in a Nanofluid - Nor Azizah Yacob; Anuar Ishak; Roslinda Nazar; Ioan Pop (Journal of Applied Mathematics)
The characteristics of fluid flow and heat transfer over a stretching vertical sheet immersed in a nanofluid are investigated numerically in this paper. Three different types of nanoparticles, namely, copper Cu, alumina Al2O3, and titania TiO2, are considered, using water as the base fluid. It is found that nanofluid with titania nanoparticles has better enhancement on the heat transfer rate compared to copper and alumina nanoparticles. For a particular nanoparticle, increasing the nanoparticle fraction is to reduce the skin friction coefficient and the heat transfer rate at the surface.